A comparative analysis of patient participation in health technology assessment systems worldwide: trends and practices - Puebla, Marcos; Korrodi-Gregório, Luis; Trentin, Luca; De Maria, Annabel; Blanqué, Nerea (Frontiers in Public Health, 2025)
IntroductionOver the last decades, Health Technology Assessment (HTA) has become pivotal in guiding decision-making concerning the inclusion of new health technologies in health systems worldwide. As HTA continues to evolve, the importance of patient participation to achieve a more informed, transparent, and legitimate decision-making process has gained increased recognition. Yet practices vary widely and are often modest in scope.MethodsWe conducted a comparison and ranking of 56 HTA systems across five regions based on levels of patient participation throughout the HTA process. Participation was measured by applying a scoring framework we developed to publicly available information for each system.ResultsMany HTA systems include patient participation, but the level of involvement shows substantial variation across systems and tends to be comparatively modest. Some systems demonstrate active engagement throughout the process, while others show limited participation.DiscussionTo our knowledge, this is the first attempt to quantify patient participation on a wider scale to enable comparisons across a large sample of HTA systems. The findings offer policymakers, healthcare professionals, patients, and researchers a comprehensive view of current approaches and highlight opportunities to enhance patient involvement in HTA.